Promoting emotional intelligence in high school students through reading comprehension in Vinces schools, 2024 - Villamar Tuarez, Betsy del Carmen; Álvarez Jorge, Aniza Maricela; Burgos Cerezo, Rosalba Marilú (SATHIRI, 2025)
Education does not focus solely on the transmission of academic knowledge; It is also crucial to promote the social and emotional competencies of future high school graduates. Consequently, emotional intelligence plays a fundamental role in the holistic advancement of people. The objective of the present study was to analyze the relationship between emotional intelligence and reading comprehension in high school students of the Isla de Bejucal de Vinces Educational Unit, 2024. The research was basic, descriptive and correlational, with a quantitative approach. It had a population of 199 students. The sample is a probabilistic sample of 132 students with an error level of 5 percent. The instruments used were the BarOn Ice Emotional Intelligence Inventory: NA, in children and adolescents (short form) and the Linguistic Complexity Reading Comprehension Test 6 Form A; instruments that have validity and reliability. The results obtained, taking into account the Pearson correlation coefficient. The hypothesis is accepted. The level of emotional intelligence and reading comprehension, R value found r = 0.133; Therefore, the alternative hypothesis is rejected and the null hypothesis is accepted. Based on the research carried out, we can conclude that there is a significant correlation between the emotional intelligence quotient and reading comprehension for high school students in the school under study.